2016
DOI: 10.4240/wjgs.v8.i9.614
|View full text |Cite
|
Sign up to set email alerts
|

Rubber band ligation of hemorrhoids: A guide for complications

Abstract: Rubber band ligation is one of the most important, cost-effective and commonly used treatments for internal hemorrhoids. Different technical approaches were developed mainly to improve efficacy and safety. The technique can be employed using an endoscope with forward-view or retroflexion or without an endoscope, using a suction elastic band ligator or a forceps ligator. Single or multiple ligations can be performed in a single session. Local anaesthetic after ligation can also be used to reduce the post-proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 61 publications
(81 reference statements)
1
56
0
3
Order By: Relevance
“…These results were confirmed by Atallah et al [157] who reveal that THD can be performed on anticoagulated patients without cessation of oral agents without an increased risk of postoperative bleeding. Nevertheless, Albuquerque [158] suggested that secondary bleeding normally occurs 10-14 days after RBL and patients taking anti-platelet and/or anti-coagulant medication have a higher risk, with some reports of massive life-threatening hemorrhage (Level of evidence: 2; Grade of recommendation: C).…”
Section: Coagulopathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were confirmed by Atallah et al [157] who reveal that THD can be performed on anticoagulated patients without cessation of oral agents without an increased risk of postoperative bleeding. Nevertheless, Albuquerque [158] suggested that secondary bleeding normally occurs 10-14 days after RBL and patients taking anti-platelet and/or anti-coagulant medication have a higher risk, with some reports of massive life-threatening hemorrhage (Level of evidence: 2; Grade of recommendation: C).…”
Section: Coagulopathiesmentioning
confidence: 99%
“…Several studies described different complication rates following office procedures (such as RBL, sclerotherapy, and infrared coagulation), ranging from 3% to 18.8% [158,178]. A review of 39 studies including 8060 patients who had RBL revealed post-banding complications in 14% of the patients, although severe complications are rarely reported [179].…”
Section: ; Grade Of Recommendation: B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Применение этого метода целесообразно на II и III стадиях геморроя, когда отсутствует выраженная дистрофия фиброзно-мышечного каркаса дистального отдела прямой кишки. Данный метод имеет невысокий процент осложнений, среди которых наиболее частыми (до 5 %) являются острые послеоперационные тромбозы наружных геморроидальных узлов [3,4]. При лечении пациентов этим методом возврат симптомов геморроя через 12 месяцев наблюдается у 10-25 % пациентов [5][6][7].…”
Section: ключевые слова: хронический комбинированный геморрой лигироunclassified
“…При сравнении наших результатов с литературными данными количество осложнений после латексного лигирования и отдаленные результаты согласуются с ними [4,7]. Так, по данным V. S. Lyer с соавторами [7], при проведении латексного лигирования острые тромбозы наружных геморроидальных узлов и другие осложнения наблюдаются с частотой до 5 % случаев.…”
Section: Abstract: Combined Haemorrhoids Ligation Of Internal Haemorunclassified